Comparative study of cohesion and adaptability in families with and without history of sexual abuse - Salazar Samillán, Silvia L. (2020)
Objective: Comparison de cohesion and adaptability levels between nuclear and transgenerational families with and without a history of sexual abuse. Material and Methods: Non-experimental, quantitative, descriptive-comparative, prospective and transversal approach. Results: Using the Mann Whitney U test for independent samples, statistically significant differences about cohesion levels were found between parents of original or transgenerational families who had suffered sexual abuse event and those who had not (U = 1578.5, z = 2.09, p = 0.037). A similar finding was seen in individual family members who were victims of abuse vs. those who did not have such experience. (U= 1616.5, z = 2.35, p = 0.019). About adaptability, statistically significant differences were found between mothers of original or transgenerational families who has suffered a sexual abuse event and those who had not (U = 1605, z = 2.07, p = 0.023). Conclusions: Patterns repeat themselves from one generation to another, triggering levels of family dysfunction, regardless of the presence or absence of a history of sexual abuse.